1994
DOI: 10.1123/jsm.8.3.200
|View full text |Cite
|
Sign up to set email alerts
|

Distributive Justice in Intercollegiate Athletics: The Views of NCAA Coaches and Administrators

Abstract: This study examined the principles of distributive justice held by male and female coaches and athletic administrators from all three NCAA divisions in allocating resources within athletic departments. A total of 328 subjects from Divisions I, II, and III responded to the instrument, which contained 12 scenarios describing situations of either distribution or retribution of three different resources-—money, facilities, or support services. The eight allocation principles listed under each scenario were (a) equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 64 publications
4
42
0
Order By: Relevance
“…The participant's perceptions regarding resource support convey that only the contribution of male athletic programs was deemed valuable to decision makers, which reflects a skewed version of the equity principle in distributive justice. Hums and Chelladurai (1994) found that administrators and coaches view the principles of equality and need as more just than the principle of equity. However, Mahony and Pastore (1998) determined that this preference is "inconsistent with actual distributions" (p. 148).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The participant's perceptions regarding resource support convey that only the contribution of male athletic programs was deemed valuable to decision makers, which reflects a skewed version of the equity principle in distributive justice. Hums and Chelladurai (1994) found that administrators and coaches view the principles of equality and need as more just than the principle of equity. However, Mahony and Pastore (1998) determined that this preference is "inconsistent with actual distributions" (p. 148).…”
Section: Discussionmentioning
confidence: 99%
“…Previously authors (e.g., Hums & Chelladurai, 1994;Patrick, Mahony & Petrosko, 2008) determined that females favor the equality principle over the equity principle, whereas men favor the equity principle over the equality principle. Equality has been identified as an objective principle whereas need is subjective (Mahony, Hums, & Reimer, 2002).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies on the perceptions of intercollegiate coaches has focused only on the perceptions of head coaches (Chelladurai & Ogasawara, 2003;Hums & Chelladurai, 1994b;Jordan et al 2004;Raedeke, Granzyk, & Warren, 2000;Whisenant & Jordan, 2006). The present study examined differences of both head and assistant coaches as assistant coaches may have different perceptions that affect both their overall job satisfaction and organizational commitment differently.…”
Section: Significance Of the Studymentioning
confidence: 86%
“…The purpose of the Dittmore NGBs as participants in the study (N = 72). A scenario based survey was designed based on prior studies on distributive justice (Hums & Chelladurai, 1994a' 1994bMahony, Hums, & Riemer, 2002;Mahony, Riemer, Breeding & Hums, 2006;Patrick, Mahony, & Petrosko, 2008). The survey consisted of three distribution scenarios where each participant was asked to rate the perceived fairness of the seven distribution principles on a 7-point Likert-type scale (1 = "very unfair", 7 = "very fair").…”
Section: Organizational Justice Outside Of Intercollegiate Athleticsmentioning
confidence: 99%